2015
DOI: 10.1088/0004-637x/810/2/105
|View full text |Cite
|
Sign up to set email alerts
|

The Solar System as an Exoplanetary System

Abstract: With the availability of considerably more data, we revisit the question of how special our Solar System is, compared to observed exoplanetary systems. To this goal, we employ a mathematical transformation that allows for a meaningful, statistical comparison. We find that the masses and densities of the giant planets in our Solar System are very typical, as is the age of the Solar System. While the orbital location of Jupiter is somewhat of an outlier, this is most likely due to strong selection effects toward… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 94 publications
1
34
0
Order By: Relevance
“…Recently, Santos et al [193] using the SWEET-Cat database also addressed the question whether very massive Jupiters tend to form at metallicities lower than their less massive counterparts. The authors found a convincing observational evidence that giant planets with masses above and below ∼4 M constitute two distinct populations 24 . They showed that the hosts of giant planets with masses < 4 M have metallicities on average higher than that of the fields stars without planets.…”
Section: Very Massive Giants and Metallicitymentioning
confidence: 96%
“…Recently, Santos et al [193] using the SWEET-Cat database also addressed the question whether very massive Jupiters tend to form at metallicities lower than their less massive counterparts. The authors found a convincing observational evidence that giant planets with masses above and below ∼4 M constitute two distinct populations 24 . They showed that the hosts of giant planets with masses < 4 M have metallicities on average higher than that of the fields stars without planets.…”
Section: Very Massive Giants and Metallicitymentioning
confidence: 96%
“…The only clear difference is in the period of the innermost planet where the solar system is an outlier. While the lack of superearths/mini-Neptunes in the solar system is also notable (Martin & Livio 2015), earth-sized planets are not intrinsically rare, and the size of the terrestrial planets does not make the solar system an outlier in the exoplanet distribution.…”
Section: How Rare Is the Solar System?mentioning
confidence: 99%
“…The vast majority of observed super-Earths are close to their parent star, although this is most likely a selection effect (Chiang & Laughlin 2013). In a recent work, Martin & Livio (2015) have shown that perhaps the main characteristic that distinguishes the solar system from the observed exoplanetary systems is the absence of super-Earths. Consequently, it is very interesting to examine the effects that the presence of a super-Earth would have had on asteroid impacts on Earth.…”
Section: Introductionmentioning
confidence: 99%